2022
DOI: 10.46743/1540-580x/2022.2109
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Human Gross Anatomy Laboratories in DPT Programs across the United States

Abstract: Purpose: The purposes of this study were to 1) describe the current teaching methodology used in Doctor of Physical Therapy (DPT) human gross anatomy (HGA) labs, 2) examine the demographics and perceptions of HGA instructors and compare responses based on years of experience, 3) determine the utilization and instructor perceptions related to cadaver dissection and other methods of instruction, and 4) determine which safety/security protocols are used in HGA laboratories. Method: All DPT programs (N=250) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In fact, there were no significant training programs, with a recent survey indicating that up to 95% of programs are still using anatomical donors and 86% of those are student dissection. 28 Similar studies were conducted in 1994 and 2013 and show that while change is occurring, it is very slow; in 1994, 100% of programs surveyed were utilizing dissection, compared with 92% in 2013. 27,29 The Mitchell study 28 and the results from our early-career participants refute the findings of a 2012 study 20 which predicted that time dedicated to learning from anatomical donors in physical therapy school would decrease by the year 2020, with a greater amount of time devoted to surface anatomy, palpation, imaging, use of prosection and computerized labs.…”
Section: Dissection Is Still the Cornerstone Of Physical Therapy Anat...mentioning
confidence: 73%
See 4 more Smart Citations
“…In fact, there were no significant training programs, with a recent survey indicating that up to 95% of programs are still using anatomical donors and 86% of those are student dissection. 28 Similar studies were conducted in 1994 and 2013 and show that while change is occurring, it is very slow; in 1994, 100% of programs surveyed were utilizing dissection, compared with 92% in 2013. 27,29 The Mitchell study 28 and the results from our early-career participants refute the findings of a 2012 study 20 which predicted that time dedicated to learning from anatomical donors in physical therapy school would decrease by the year 2020, with a greater amount of time devoted to surface anatomy, palpation, imaging, use of prosection and computerized labs.…”
Section: Dissection Is Still the Cornerstone Of Physical Therapy Anat...mentioning
confidence: 73%
“…A survey of physical therapists' gross anatomy experiences found that 90% of instructors felt anatomical donors were the best way to learn and 60% felt they were the only way to learn. However, less experienced faculty were more likely to believe that a dissection‐free approach can be just as effective for learning 28 . Dissection is frequently lauded for exposing students to their first provider‐patient relationship, teamwork, professionalism as well as concepts of death and dying and dealing with complex emotions 40 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations